Rainfall trend analysis and precipitation concentration index in synoptic stations of Urmia Lake Basin - ayub mirzayi; hirad abghari; mehdi erfanian (جغرافیا و توسعه, 2020)
The lake Urmia has been experiencing rainfall severe fluctuations in the recent years, as water level elevation of the lake Urmia has declined that some of the researchers rainfall reduction is one of the main reasons that it seems to be important to investigate the changes in the monthly and annual precipitation of lake Urmia basin. In this study, monthly, seasonal, annual rainfall and precipitation concentration index at annual and seasonal scale in synoptic stations (Tabriz, Urmia, Takab, Mahabad, Ahar, Sarab, Sahand, Mianeh) in lake Urmia basin from years (1988-2013) was investigated. Then to analysis the rainfall trend and PCI index of the Mann-Kendall and Slope-Sen test were used for identify mutation points. The results showed that among the synoptic stations seven studied, a non-significant reduction trend and stations two (Tabriz and Sarab) had a non-significant increasing trend. most of the synoptic stations of lake Urmia have been observed monthly precipitation in the months (january, november, december)as well as in the months (May, August, september) has been increased in most stations. Based on Sen - Thile test and at %95 confidence level, maximum and minimum amount of annual rainfall decrease occurred in mahabad and Urmia station, respectively. None of the synoptic stations had a uniform temporal distribution (PCI <10) and only the Ahar station has an average annual rainfall distribution. Seasonal precipitation trend analysis showed that in winter the supply of large part of lake Urmia water requirement, most of synoptic stations have reduction trend.